Mountain invasions on the way: are there climatic constraints for the expansion of alien woody species along an elevation gradient in Argentina? - Tecco, Paula Andrea (2015)
Aims Increasing evidence worldwide indicates that high mountain regions are not immune to invasion by alien plants. Here we aimed to address whether three major woody invaders of low-mountain areas are constrained to lower altitudes due to climatic restrictions or just by low propagule pressure. We hypothesize that the increasing climatic harshness towards higher altitudes restricts seedling establishment and survival of these woody invaders and thus their potential for altitudinal expansion.Methods The study was carried out in the Sierras Grandes Mountains, Córdoba, central Argentina (32º 50?S, 64º 90?W). We addressed the hypothesis with an experimental approach, dissociating the effect of the environmental gradient from that of propagule pressure, by discarding the influence of seed sources. We translocated seeds of Gleditsia triacanthos L., Ligustrum lucidum W.T. Aiton. and Pyracantha angustifolia (Franch.) C.K.Schneid. along the altitudinal gradient (from 900 to 2700 m asl). Seven sites were selected along the altitudinal gradient, spaced every 200?400 m. Three plots (4 x 4 m) were selected within each altitudinal site and excluded from livestock; 100 seeds of each species were sown within each plot (6300 seeds in total). Seedling emergence and survival was monitored during two growing seasons and soil temperature and moisture was recorded as well. The field experiment was complemented with lab assays.Important Findings: Climate along this altitudinal gradient might be least restrictive at mid elevations, as a result of the intersection between opposite soil temperature and moisture gradients. Sown seeds germinated along the whole altitudinal gradient and seedlings successfully established and over-wintered well above their current altitudinal distribution (up to 2200 m for Ligustrum and 2400 m for Gleditsia and Pyracantha). Additional lab assays confirmed field patterns and gave some insights into contrasting regeneration strategies between these invaders that might help to overcome stochastic environmental constraints in the germination stage. Overall, seedlings of three major woody invaders of low-mountain woodlands can establish and survive at higher elevations than their current distribution. In contrast to natives, they seem to be broad climate tolerators, rather than specialized stress tolerators, capable of germinating and growing across a wide elevational range. While long term experiments might be necessary to fully address the potentials for altitudinal expansion, out results on early lifecycle stage suggest that the invaders studied here would have mostly a dispersal barrier rather than a climate barrier to establish in the upper belt of the Sierras Grandes.